The Influence of Work Motivation, Work Environment, Work Culture, and Work-Life Balance on Gen Z Employee Perfomance in Jakarta - Titi Indri; Karyn Desvrilla; Christyna Capriaty; Shandy Puspita (Primanomics : Jurnal Ekonomi & Bisnis, 2026)
Human Resources (HR) is the key to a company’s success, where employee performance is the main reflection. The challenges of managing HR are increasingly complex as the population grows rapidly, especially with the arrival of Generation Z (birth years 1997-2012) who now dominate the workforce. Known for their high adaptability and digital skills, Generation Z is not free from obstacles. A survey noted companies dissatisfaction with their performance. Therefore, this study was conducted to re-examine the determinants of Generation Z performance, by adding work-life balance as a new independent variable, in line with the recommendations of previous research on work motivation, work environment and work culture. The results of this study indicate that work motivation, work environment, work culture and work life balance have a positive and significant influence on the performance of Generation Z employee in Jakarta.